2020
DOI: 10.48550/arxiv.2006.12096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective coupling conditions for arbitrary flows in Stokes-Darcy systems

Abstract: Boundary conditions at the interface between the free-flow region and the adjacent porous medium is a key issue for physically consistent modeling and accurate numerical simulation of flow and transport processes in coupled systems due to the interface driven nature of such processes. Interface conditions available in the literature have several weak points: most of them are suitable only for flows parallel to the fluid-porous interface, some are restricted to specific boundary value problems, and others conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Remark 1. We note that the Beavers-Joseph-Saffman boundary conditions were found experimentally in (Beavers and Joseph, 1967;Saffman, 1971) and demonstrated in Mikelić, 2000, 2009), but only in a 2D laminar case (as mentioned in (Auriault, 2010)), and the extension to a generic geometry is non-trivial (Eggenweiler and Rybak, 2021). Moreover, in (Auriault, 2010) they found that the corrector of the simplified boundary condition (12) is ϵ 2 .…”
Section: Mathematical Modelmentioning
confidence: 66%
“…Remark 1. We note that the Beavers-Joseph-Saffman boundary conditions were found experimentally in (Beavers and Joseph, 1967;Saffman, 1971) and demonstrated in Mikelić, 2000, 2009), but only in a 2D laminar case (as mentioned in (Auriault, 2010)), and the extension to a generic geometry is non-trivial (Eggenweiler and Rybak, 2021). Moreover, in (Auriault, 2010) they found that the corrector of the simplified boundary condition (12) is ϵ 2 .…”
Section: Mathematical Modelmentioning
confidence: 66%